The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2478/achi-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Spion-CDs as a Multifunctional Fluorescence/Magnetic Resonance Nanoparticle

Abstract: A multifunctional nanoparticle, Super Paramagnetic Iron Oxide Nanoparticle-Carbon Dots (SPION-CDs), for fluorescence and magnetic resonance imaging is introduced. This nanoparticle possesses the magnetic properties of super-paramagnetic iron oxide (SPION) core as well as the fluorescence characteristics of carbon dots (CDs) coated in mesoporous structure. The SPION-CDs were synthesized using a high temperature facile single-pot hydrothermal method. The products were characterized by transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Our studies showed that their effects on cells depend on the cell type, cluster design and concentration [ 158 159 ]. Asgari et al [ 160 ] produced 50 nm SPION–carbon dot nanoparticles, which were designed for MRI and fluorescence imaging with good cytocompatibility. Park et al [ 161 ] synthesized SPIONs coated with folate containing 64 Cu for positronic emission tomography and MRI.…”
Section: Reviewmentioning
confidence: 99%
“…Our studies showed that their effects on cells depend on the cell type, cluster design and concentration [ 158 159 ]. Asgari et al [ 160 ] produced 50 nm SPION–carbon dot nanoparticles, which were designed for MRI and fluorescence imaging with good cytocompatibility. Park et al [ 161 ] synthesized SPIONs coated with folate containing 64 Cu for positronic emission tomography and MRI.…”
Section: Reviewmentioning
confidence: 99%